1988
DOI: 10.1007/bf02370110
|View full text |Cite
|
Sign up to set email alerts
|

Yields and nitrogen nutrition of intercropped maize and ricebean (Vigna umbellata [Thumb.] Ohwi and Ohashi)

Abstract: Maize (Zea mays L.) and ricebean (Vigna umbellata [Thumb.] Ohwi and Ohashi) were grown in intercrop and monoculture on Tropaqualf soils under rainfed conditions in Northern Thailand yearly from 1983 to 1986. De Wit's replacement design was used to compare intercrops and monocultures with a constant plant density equivalent to 80000 maize or 160000 ricebean plantsha -~. Combined nitrogen was applied at varying levels to 200 kg N ha ~. In the final two seasons the intercrop ratio of maize: ricebean was also vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…The 'indirect' pathway of N transfer via mineralisation of residues and uptake by the non-legume crop is comparatively understood, direct transfer pathways are less well understood (Peoples et al, 2015). Our results agree with studies that reported that cowpeas (Vigna unguiculata) in field and glasshouse experiments and ricebeans (Vigna umbellata) in a field trial did not appear to directly transfer N to maize (Rerkasem andRerkasem, 1988, Ofori andStern, 1986). Similarly, reviews on the topic have concluded that contribution of direct N transfer are minor or negligible (Peoples and Herridge, 1990).…”
Section: Effects Of Soybean On Sugarcane Biomass and Nitrogen Accumulsupporting
confidence: 88%
“…The 'indirect' pathway of N transfer via mineralisation of residues and uptake by the non-legume crop is comparatively understood, direct transfer pathways are less well understood (Peoples et al, 2015). Our results agree with studies that reported that cowpeas (Vigna unguiculata) in field and glasshouse experiments and ricebeans (Vigna umbellata) in a field trial did not appear to directly transfer N to maize (Rerkasem andRerkasem, 1988, Ofori andStern, 1986). Similarly, reviews on the topic have concluded that contribution of direct N transfer are minor or negligible (Peoples and Herridge, 1990).…”
Section: Effects Of Soybean On Sugarcane Biomass and Nitrogen Accumulsupporting
confidence: 88%
“…7)] and the resuits from other mSN experiments (Rerkasem, and Rerkasem, 1988) showed that the proportion of legume N derived from N2 was higher in ricebean grown in association with maize than when grown as a sole crop. The stimulation of symbiotic activity and suppression of uptake of soil N by ricebean contributed to an increase in total crop N in maize:ricebean intercrops (Figs.…”
Section: Resultsmentioning
confidence: 96%
“…Eaglesham et al (1981) and Hamel et al (1991) suggest that transfer is via legume excretion and subsequent maize uptake rather than by direct transfer. Maize can also benefit as a result of the legume taking less soil nitrogen, as indicated by Rerkasem and Rerkasem (1988) and Martin et al (1991). Further studies are required to determine to what extent the benefit to the maize was due to nitrogen transfer from the bean and to what extent it was due to reduced competition by the bean for the scarce soil nitrogen pool.…”
Section: Discussionmentioning
confidence: 99%